PENGARUH GREEN MARKETING TERHADAP GREEN BUYING BEHAVIOR THE BODY SHOP; GREEN CONSUMPTION SEBAGAI PEMEDIASI - Zulmar, Dwi Yudhi; Sari, Astri Yuza (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2025)
This study aims to analyze the influence of environmentally oriented marketing on environmentally friendly purchasing behavior, with green consumption as a mediating variable. The research subjects are consumers of The Body Shop in Padang City, West Sumatra. A quantitative approach was employed, with data collected through questionnaires distributed to 145 respondents. The data were analyzed using SmartPLS software. The findings indicate that environmentally friendly marketing has a positive and significant effect on both green consumption and environmentally friendly purchasing behavior. Furthermore, green consumption also has a positive effect on environmentally friendly purchasing behavior and mediates the relationship between environmentally friendly marketing and purchasing behavior. The study reveals four main points: (1) green consumption positively influences environmentally friendly purchasing behavior, (2) environmentally oriented marketing strategies have a positive effect on environmentally friendly purchasing behavior, (3) environmentally friendly marketing directly impacts purchasing decisions, and (4) green consumption acts as a mediator. The practical implications of this research highlight the importance for companies, particularly in the beauty and personal care sector, to integrate sustainability messages into their marketing strategies in order to encourage more environmentally conscious consumption and purchasing behavior